2019
DOI: 10.1093/erae/jbz045
|View full text |Cite
|
Sign up to set email alerts
|

Analysing group contract design using a threshold public goods experiment

Abstract: This paper presents the results of a threshold public goods game experiment with heterogeneous players. The experiment is designed in close collaboration with the Dutch association of agri-environmental farmer collectives. Subjects are recruited at a university (study 1) and a farm management training centre (study 2), the subjects of the second study most resembling the subjects in the field. The experiment consists of several treatments and each treatment has two different distribution rules, which are varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A brief review of the publications revealed research trends that are relevant both for the Russian South with traditionally developed farming and for other regions of the world. Moreover, the general conclusion is the need for the development of farming to ensure the food security of countries, the preservation of rural populations and the development of rural areas, the introduction of new technological processes, institutional transformations, ensuring the quality of agricultural products, the environmental validity of managerial decisions in small-scale agricultural production [8,9,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…A brief review of the publications revealed research trends that are relevant both for the Russian South with traditionally developed farming and for other regions of the world. Moreover, the general conclusion is the need for the development of farming to ensure the food security of countries, the preservation of rural populations and the development of rural areas, the introduction of new technological processes, institutional transformations, ensuring the quality of agricultural products, the environmental validity of managerial decisions in small-scale agricultural production [8,9,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Public goods games are a commonly applied methodology to study cooperation in experimental economics (for a meta-analysis of lab studies, see Zelmer 36 ). There is a quickly growing literature on applying and co-designing public goods games with field populations, 37 also involving workshop formats. 38 In a standard linear contribution mechanism of public goods game experiment, n players receive an endowment e , which they must allocate to a private and public account.…”
Section: Adjustments Made To Methods In Methodological Toolkitmentioning
confidence: 99%
“…Within this set up, CCV showed that increasing the number of public goods resulted in miscoordination among donors, lower contributions and a lower probability that any public good reached its contribution threshold. Several papers since have looked at extensions of CCV (Ansink, Koetse, Bouma, Hauck, & van Soest, 2017;Bouma, Nguyen, Van Der Heijden, & Dijk, 2020;Cason & Zubrickas, 2019). CCR extended CCV by introducing the possibility of coordinating contributions via an intermediary, varying whether the intermediary was obliged to send all transfers received from donors to the public goods as opposed to being allowed to expropriate any amount of these transfers for herself, and finding only that the former had a positive effect on public good success.…”
Section: Related Literaturementioning
confidence: 99%